Halal Product Development - Gunawan Anugra Sumule, Joshua; Sihaloho, Serli; Pangaribuan, Ika S; SW, Oman Fathurohman; Salamah, Nina (Riwayat: Educational Journal of History and Humanities, 2025)
The Indonesian Ulema Council (MUI) plays a pivotal role in supporting producers to ensure their products comply with sharia standards, addressing challenges that extend beyond market competitiveness to align with Islamic law. This study adopts a qualitative approach to analyze halal product development, focusing on critical elements such as logistics, certification, and community-based verification. The research highlights the roles of MUI and local communities in upholding halal standards throughout the production and distribution processes. Halal is defined as the appropriateness, legality, and permissibility of a product according to Islamic law, and key concerns include preventing contamination during distribution, ensuring compliance with religious provisions, and raising awareness through community participation. The study also underscores the significance of integrating logistical systems, effective certification processes, and active community engagement in promoting halal products. By adopting a holistic strategy, Indonesia can strengthen its halal industry, ensuring products not only meet sharia standards but also increase competitiveness in the global market. This approach highlights the importance of collaboration between various stakeholders, including producers, MUI, and local communities, in ensuring the sustainable growth of Indonesia's halal sector while fostering greater understanding and acceptance of halal practices worldwide.